SINERGI MANAJEMEN SUMBER DAYA MANUSIA (SDM) DALAM RANGKA PENINGKATAN KINERJA KARYAWAN DI RUMAH SAKIT AMERTA HUSADHA - Wayan Hari Premananda (Nusantara Hasana Journal, 2025)
In managing human resource management (HR) to achieve effective and efficient employee performance, synergy is needed to be able to influence success in achieving the vision and mission of an institution, especially a hospital. This study aims to describe and clearly illustrate how HR management synergy is needed for the effectiveness and efficiency of employee performance at Amertha Husada Hospital. This study uses a descriptive qualitative method. The results of this study indicate that from the SWOT analysis, there is a strength where the hospital is able to recruit professional experts, but with internal shortcomings, namely long adjustments. Externally, there are many opportunities, one of which is collaboration with other institutions and organizations to recruit good experts, but with threats, namely state regulations and the presence of other hospitals. Therefore, periodic evaluation, supervision and recognition of performance by providing rewards to employees are needed so that they can provide good performance in achieving the hospital's vision and mission.